REPRESSION AND DISPLACEMENT OF MAIN CHARACTER IN ELIZABETH GILBERT’S NOVEL EAT, PRAY, LOVE (A PSYCHOLOGICAL ANALYSIS) - Octhaviani Octhaviani; Muhammad Natsir (LINGUISTICA, 2014)
ABSTRACT   This study deals with Repression and Displacement of Main Character in Elizabeth Gilbert’s Novel Eat, Pray, Love. The objectives of this study were to find out the causing of repression and the displacement in the novel. This study was limited to analyze Liz as the main character. This study applied descriptive qualitative method. The data were taken from Elizabeth Gilbert’s novel Eat, Pray, Love. The findings indicated that Liz got repressions which are triggered by two factors; the crisis of self identity and marriage conflict. And then the displacement that occurred to the main character after getting repressions were losing faith about marriage, disorder eating habit, and converting new orientation of spiritual life.   Keyword        :  repression, displacement, character, novel